Sociodemographic and psychosocial factors influencing Long-Term Contraceptive Method (LTCM) uptake among Indonesian women: A mixed-methods study - Hayuning Tiyas, Ajeng; Amin, Erna; Anwar, Yulianti (Utan Kayu Publishing, 2025)
Despite the high effectiveness of long-term contraceptive methods (LTCM), participation rates in Indonesia—particularly in Mamuju—remain well below national targets, highlighting an urgent public health gap. This study addresses this issue by investigating the interplay of sociodemographic and psychosocial determinants shaping women’s decisions to adopt LTCM, using a sequential explanatory mixed-methods design. A total of 120 women of reproductive age were purposively sampled for quantitative analysis, followed by in-depth interviews with 10 diverse informants. Quantitative findings identified parity as the most influential factor: women with three or more children were over nine times more likely to use LTCM, followed by age over 35, knowledge, and husband’s support, while higher education showed an inverse association. Psychosocial variables such as value of children and perception of the ideal family, though culturally significant, did not independently predict LTCM use. Qualitative insights revealed that husband’s approval and practical economic or health concerns often outweighed cultural ideals. These results suggest that interventions must prioritize tailored IEC for high-parity and older women, empower male partners, and strengthen service accessibility. Family planning programs in similar contexts should integrate couple-based counseling and community engagement to drive LTCM uptake and address persistent gaps in reproductive health outcomes.